Sacral kingship between disenchantment and re-enchantment : the French and English monarchies 1587-1688. - Asch, Ronald G. (Studies in British and imperial history, 2014)
France and England are often seen as monarchies standing at opposite ends of the spectrum of seventeenth-century European political culture. On the one hand the Bourbon monarchy took the high road to absolutism, while on the other the Stuarts never quite recovered from the diminution of their royal authority following the regicide of Charles I in 1649. However, both monarchies shared a common medieval heritage of sacral kingship, and their histories remained deeply entangled throughout the century. This study focuses on the interaction between ideas of monarchy and images of power in the t.